2012
DOI: 10.1523/jneurosci.3413-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

No Dissociation between Perception and Action in Patient DF When Haptic Feedback is Withdrawn

Abstract: Goodale et al. (1991) reported a striking dissociation between vision for perception and action. They examined DF, a human patient who had damage to her ventral visual stream and suffered from visual form agnosia. She was unable to perceive an object's size but could match the opening of her hand to the object's size during grasping. It was concluded that grasping relied on a separate representation of visual size in the dorsal stream and required no visual input from the ventral stream. This observation inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
108
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 28 publications
6
108
2
Order By: Relevance
“…However, even when haptic feedback was available throughout the block, the MGA was subject to the same depth constancy failure observed during Pretraining and Posttraining blocks. This second compelling result concerning the similarity between perceptual biases and biases observed for reach-to-grasp actions endorses the hypothesis that processing of visual information for both perceptual judgments and visually guided actions is indicative of similar and interrelated underlying mechanisms (Foster et al 2011;Franz et al 2000Franz et al , 2009Franz and Gegenfurtner 2008;Schenk 2010Schenk , 2012. In particular, the present findings would indicate that depth scaling of binocular disparities is the same for perception and action, a result incompatible with the dual visual systems theory (Goodale et al 1991;Goodale and Milner 1992).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, even when haptic feedback was available throughout the block, the MGA was subject to the same depth constancy failure observed during Pretraining and Posttraining blocks. This second compelling result concerning the similarity between perceptual biases and biases observed for reach-to-grasp actions endorses the hypothesis that processing of visual information for both perceptual judgments and visually guided actions is indicative of similar and interrelated underlying mechanisms (Foster et al 2011;Franz et al 2000Franz et al , 2009Franz and Gegenfurtner 2008;Schenk 2010Schenk , 2012. In particular, the present findings would indicate that depth scaling of binocular disparities is the same for perception and action, a result incompatible with the dual visual systems theory (Goodale et al 1991;Goodale and Milner 1992).…”
Section: Discussionsupporting
confidence: 78%
“…In the latter cases, the action is shown to be subject to the different biases similar to those found in perceptual tasks, leading to the assumption that different perceptual processes are engaged depending on the different feedback available (Goodale et al 1994;Whitwell et al 2014). Then again, what these studies show is an undeniable inaccuracy in object depth and distance estimates in the absence of haptic feedback, supporting the key role the haptic feedback has in grasping actions Schenk 2012;Whitwell et al 2014). Nevertheless, the present findings demonstrate that also in the presence of all sensory feedback, haptic and visual, depth constancy is still compromised.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our sense of touch, for example, is critical for a range of behaviors, from simple manual localization (Rao and Gordon 2001) to complex object interaction. Indeed, recent work has even suggested that haptic feedback might underpin the apparent skill with which the famous visual form agnosic patient DF grasps objects that she cannot visually distinguish (Schenk 2012; see Whitwell and Buckingham 2013 for discussion). It is clear that the role of haptic feedback in sensorimotor control is complex and relatively understudied.…”
mentioning
confidence: 99%